The trajectories of Christianity and African ritual practices: the public silence and the dilemma of mainline or mission churches - L. Ntombana (Acta Theologica)
In South Africa, there are mainly two Christian traditions on Christianity and African ritual practices. One being from missionaries and now mainly trailed by most white Mainline Churches and Pentecostal Churches. The other is by African Independent Churches (AIC). The first group oppose and condemn Christian involvement on any rituals related to ancestors. However, the second group perceive no conflict between Christianity and African rituals. This paper presents a brief discussion on the beliefs and views of various Christian groups on African rituals, focusing mainly on black members of the Mainline Churches. In this paper I examine literature from the 18th century and also revisit my ethnographic work which focuses on this theme in the democratic South Africa. Findings of this study suggests that black members of mainline Churches are still caught in between two identities; one being the Western package of Christianity and the African ritual practices.